2015
DOI: 10.1063/1.4922300
|View full text |Cite
|
Sign up to set email alerts
|

Minima of the fluctuations of the order parameter of global seismicity

Abstract: Minima of the fluctuations of the order parameter of global seismicity. Chaos, volume 25 (Article number 063110) and may be found at http://dx.doi.org/10.1063/1.4922300 . Copyright © and MoralRights are retained by the author(s) and/ or other copyright owners. A copy can be downloaded for personal non-commercial research or study, without prior permission or charge. This item cannot be reproduced or quoted extensively from without first obtaining permission in writing from the copyright holder(s). The content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 80 publications
2
42
0
Order By: Relevance
“…In this section, we present the results of ECA for the interrelation between the strong (target) EQs and the order parameter fluctuation minima β min that have been found in the regional studies of Japan [59], Eastern Mediterranean [62], and in the global seismicity [60,61], see Figure 1. For these reasons, the time-series of target EQs will serve as event time-series A and the time-series of β min as event time-series B, whereas the unit of time for ∆T and τ is one day.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this section, we present the results of ECA for the interrelation between the strong (target) EQs and the order parameter fluctuation minima β min that have been found in the regional studies of Japan [59], Eastern Mediterranean [62], and in the global seismicity [60,61], see Figure 1. For these reasons, the time-series of target EQs will serve as event time-series A and the time-series of β min as event time-series B, whereas the unit of time for ∆T and τ is one day.…”
Section: Resultsmentioning
confidence: 99%
“…The time evolution of β W is followed by sliding the window of W consecutive EQs, event by event, through the EQ catalog and assigning to its value the occurrence time of the EQ which follows the last EQ of the window studied in the EQ catalog. The fluctuations of the order parameter of seismicity as quantified by β W have been studied in various seismically active regions, like Japan [30,31,59] or Eastern Mediterranean [62], and in the global seismicity as well [60,61]. These studies have revealed that before strong EQs β W s exhibit characteristic minima labeled β min and were focused, so far, on a small number of the stronger EQs in each geographic region (see Tables 1-5…”
Section: Natural Time Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, great tsunamis or large earthquakes (M > 8.0) are usually generated whenever extensive areas of the subduction megathrust face a rupture [1]. There are examples of earthquake-produced tsunamis in the 2004 Sumatra earthquake (M-9.0) [2], accounting for 220,000 casualties, or in 2006, with the tsunami that developed from the Java earthquake (M-7.8) [3]. The intensity and destruction capacity of earthquakes and tsunamis are estimated by considering the area of vertical uplift of the sea bed, and these magnitudes are related to the geometry of the slipping fault when the earthquake rupture is located near the sea floor [4].…”
Section: Introductionmentioning
confidence: 99%